Bad Piano? Bad Music? A Response to Comments on Lowe and Pemberton, The Official History of the British Civil Service, Volume II: 1982–1997. Issue 1 (9th March 2021) - Pemberton, Hugh
Abstract: The reforms made to the civil service during the premierships of Margaret Thatcher and John Major were unparalleled in scope in peacetime. Undertaken in the name of efficiency and better management, they served to Balkanise the service, shrink the number of civil servants, subordinate them to the will of ministers, and effectively privatise a swathe of public services. Their legacy, however, was a relatively weak centre struggling to cope with a fragmented and extremely complex governmental machine, an overly managerialist senior civil service sometimes side‐lined from policy making, and a system lacking slack as a consequence of the quest for 'efficiency' and dependent on private contractors of sometimes dubious worth. Over the past five years that legacy left the country poorly placed to triumph over the challenges of Brexit and then of Covid‐19.